STRATEGI PENGEMBANGAN USAHA KRIPIK UBI PADA KELOMPOK USAHA OPANG MADANGU DI DESA BIDIPRAING KECAMATAN LEWA TIDAHU KABUPATEN SUMBA TIMUR - Padaraga, Umbu Laura; Wadu, Junaedin (Fakultas Pertanian, Universitas Janabadra, 2024)
This research aims to analyze internal and external problems consisting of strengths, weaknesses, opportunities and threats as well as strategies for developing the sweet potato chips business in the Opang Madangu business group in Bidipraing Village, Lewa Tidahu District, East Sumba. This type of research uses descriptive and quantitative research methods. This research involved 12 informants. The accidental sampling method was used. The data analysis method used is SWOT analysis to determine the evaluation matrix of internal factors (IFE), external factors (EFE), internal-external (IE), strengths, weaknesses, opportunities, threats (SWOT), and strategic plans, as well as a quantitative matrix (QSPM). The research results show that the internal element which is the most important strength is the abundance of raw materials, and the biggest weakness is the lack of knowledge, and the external factor which is the biggest opportunity is cooperation from other industries or market partners. The biggest threat to the sweet potato chips business in the Opang Madangu business is consumer taste changes. The main strategy for developing Opang Madangu commercial chips is product innovation so that consumers have more diverse choices.